2015
DOI: 10.1074/jbc.r114.581249
|View full text |Cite
|
Sign up to set email alerts
|

SPASM and Twitch Domains in S-Adenosylmethionine (SAM) Radical Enzymes

Abstract: S-Adenosylmethionine (SAM, also known as AdoMet) radical enzymes use SAM and a [4Fe-4S] cluster to catalyze a diverse array of reactions. They adopt a partial triose-phosphate isomerase (TIM) barrel fold with N-and C-terminal extensions that tailor the structure of the enzyme to its specific function. One extension, termed a SPASM domain, binds two auxiliary [4Fe-4S] clusters and is present within peptide-modifying enzymes. The first structure of a SPASM-containing enzyme, anaerobic sulfatase-maturating enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(186 citation statements)
references
References 61 publications
7
179
0
Order By: Relevance
“…However, there are known “SPASM” domains that only contain one [4Fe-4S] cluster, which have been dubbed “twitch” domains. 11 Additional studies are required clarify the roles of these auxiliary clusters in AlbA and other SPASM-domain containing rSAM proteins.…”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…However, there are known “SPASM” domains that only contain one [4Fe-4S] cluster, which have been dubbed “twitch” domains. 11 Additional studies are required clarify the roles of these auxiliary clusters in AlbA and other SPASM-domain containing rSAM proteins.…”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…Electron paramagnetic resonance spectroscopy revealed the presence of two [4Fe–4S] clusters in SkfB. One of the clusters was coordinated by a canonical Cys-containing motif commonly present in radical-SAM enzymes while the second cluster was located within a SPASM (subtilisin A/pyrroloquinoline quinone/anaerobic sulfatase/mycofactocin maturation enzyme) domain (Flühe et al, 2013, Grell et al, 2015, Haft and Basu, 2011). Mutational studies showed one of the [4Fe–4S] clusters to be involved in the generation of the characteristic 5′-dA • radical.…”
Section: Introductionmentioning
confidence: 99%
“…Radical SAM proteins use the reductive cleavage of S-adenosyl methionine to initiate free radical chemistry, and can accomplish a wide variety of reactions, including carbon-carbon bond formation (8,9). PqqE is a founding member of the SPASM domain-containing radical SAM proteins, which contain one or more auxiliary clusters in their C-terminal regions, and of which several are known to modify small peptides or proteins (10,11). Recently, a small (ϳ10 kDa) protein, PqqD, has been shown to form a strong, sub-micromolar K D complex with the peptide substrate PqqA.…”
Section: Pyrroloquinoline Quinone (Pqq)mentioning
confidence: 99%